Peran lembaga pengelolaan dana pendidikan lembaga pengembangan dalam meningkatkan kualitas SDM Indonesia - Fajar Harguna Endra; Putra Deden Edi; Marhamah Marhamah; Suryani Suryani; Popi Puadah (SAP (Susunan Artikel Pendidikan), 2025)
Improving the quality of human resources (HR) is one of the main priorities in efforts to achieve the vision of developing Indonesia so that it is competitive in the global arena. In the era of globalization and rapid technological development, the need for superior, competent, and adaptive HR is increasingly urgent. To meet these needs, education plays a very strategic role as the main foundation in forming quality HR. One of the major challenges in managing education in Indonesia is the limited access and funding support for the community to continue their education to a higher level, especially for those who have academic potential but come from disadvantaged economic backgrounds. Realizing this, the government, through the Education Fund Management Institute (LPDP), has taken strategic steps to provide financial support in the form of scholarships and research funding aimed at improving the quality of Indonesian HR. This study uses a qualitative approach, which is an approach taken to find out or describe the reality of the events being studied so that it is easier to obtain objective data. Research objectives The synergy between APBN funds and LPDP funds also needs to be reviewed to ensure maximum benefits for national education.